Impact of Business Plans for the Development of MSMEs - Irwan Sugiarto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to determine the impact of business planning for the development of MSMEs. The research method uses is a qualitative method with a descriptive and explorative descriptive approach. From the results of the research conducted, the results show that proper business planning and the application of a good marketing strategy have a positive impact on the sustainability of MSME activities. In addition, the quality of production that has a competitive advantage is also one of the driving factors. For the development of MSMEs, there are several obstacles faced, especially related to capital and guidance from the local government. With the development of MSMEs, it is expected to improve people's welfare, including helping the government in reducing unemployment.